A hybrid cost estimation framework based on feature-oriented data mining approach. Issue 3 (August 2015) - Sajadfar, Narges; Ma, Yongsheng
Highlights A new cost estimation method combining feature-based engineering concept with data mining algorithms. Leverages empirical linear regression and data-mining algorithms with historical data. Considers gradual implementation in phases while building up the data mining capability. A case study shows steps determining the costs of the example welding features. Aiming for a highly practical solution for applications.